Bibliometrix analysis of information sharing in social media - Alhamzah F. Abbas; Ahmad Jusoh; Adaviah Mas'od; Ahmed H. Alsharif; Javed Ali (Cogent Business & Management, 2022)
Social media has evolved at a rapid pace, influencing every aspect of the global community. The purpose of this paper is to use bibliometric analysis tools to evaluate valid works on the relationship between social media and information sharing. A review study of research papers on social media and information sharing published between 2009 and 2020 was conducted. The bibliometric analysis identified the following characteristics: (1) the primary articles are based on information sharing through social media; (2) the main authors deal with information sharing in social media; (3) the newestrend topics related to information sharing in social media are demographic characteristics, cognition, sentiment, healthcare, products and services recommendations, tourist recommendations, and COVID-19. The results show significant impact rates in studies of information sharing in social media. Overall, this study serves as a basis for new scientific questions that will contribute to the further development of this research field.
Keywords: 650; bibliometrix; biblioshiny; information sharing; R packages; social media